Livelihoods and Food Security Among Rural Households in the North-Western Mount Kenya Region - Mutea, Emily; Bottazzi, Patrick; Jacobi, Johanna; Kiteme, Boniface; Speranza, Chinwe Ifejika; Rist, Stephan (Frontiers in Sustainable Food Systems, 2019)
Food insecurity remains a major concern for numerous rural households in Sub-Saharan Africa who rely on agriculture as their main source of livelihood. The assessment of the links between food security and livelihoods is central for overcoming widespread food insecurity. However, assessments remain challenging due to food security’s multi-dimensionality and the challenge of finding indicators that are comparable and applicable to various contexts. This study addresses this challenge by adapting a food security index (FSI) and uses it to assess the livelihood drivers of food security. The index captures the multi-dimensionality of food security using conventional food security indicators. The assessed indicators include measures of “food consumption score”, “household dietary diversity score”, “coping strategies index”, the “household food insecurity access scale” and “months of adequate household food provisioning”. The study covered 600 randomly selected households representative of three agro-ecological zones located close to large-scale agricultural investment in Mount Kenya region in Kenya. We used linear regression to identify livelihood factors significantly influencing food security. Spearman’s rank-order correlation and student’s T-test demonstrated a strong and significant correlation between the composite FSI index and each classical indicators of food security. Overall, 32% of the households were food secure and 68% were food insecure. Households’ ownership of productive hand tools, followed by off-farm income, consumption of own produced food, type of agro-ecological zone, farm income and number of main crops infested by pests had a significant effect on household food security. All these factors, except the number of main crops infested by pests, positively influenced household food security. Households in humid agro-ecological zone were less food secure than households in semi-humid and semi-arid zones. Household size, the size of accessible land and households’ members’ participation to large agricultural investments (as wage workers or sub-contract farmer) were not significantly influencing food security. Households of the Mount Kenya region need alternative off-farm income sources combined with further support to improve sustainable agriculture management with appropriate hand tools for increased production, and improve value chains to increase farm income.